Four novel mutations in the ALPL gene in Chinese patients with odonto, childhood, and adult hypophosphatasia - Xu, Lijun (Biosci Rep, 2018)
Hypophosphatasia (HPP) is a rare inherited disorder characterized by defective bone and/or dental mineralization, and decreased serum alkaline phosphatase (ALP) activity. ALPL, the only gene related with HPP, encodes tissue non-specific ALP (TNSALP). Few studies were carried out in ALPL gene mutations in the Chinese population with HPP. The purpose of the present study is to elucidate the clinical and genetic characteristics of HPP in five unrelated Chinese families and two sporadic patients. Ten clinically diagnosed HPP patients from five unrelated Chinese families and two sporadic patients and fifty healthy controls were genetically investigated. All 12 exons and exon–intron boundaries of the ALPL gene were amplified by PCR and directly sequenced. The laboratory and radiological investigations were conducted simultaneously in these HPP ten patients. A 3D model of the TNSALP was used to predict the dominant negative effect of identified missense mutations. Three odonto, three childhood, and four adult types of HPP were clinically diagnosed. Ten mutations were identified in five unrelated Chinese families and two sporadic patients, including eight missense mutations and two frameshift mutations. Of which, four were novel: one frameshift mutation (p.R138Pfsx45); three missense mutations (p.C201R, p.V459A, p.C497S). No identical mutations and any other new ALPL mutations were found in unrelated 50 healthy controls. Our study demonstrated that the ALPL gene mutations are responsible for HPP in these Chinese families. These findings will be useful for clinicians to improve understanding of this heritable bone disorder.